(untitled) (Bangladesh Journal of Medical Science, 2017)
Objective: To investigate the frequency of metabolic syndrome (MetS) in patients with acrochordons. Materials and Methods: 102 patients with acrochordons and 76 controls were enrolled into the study. The presence of MetS was evaluated under the criteria NCEP-ATP III. Results and Discussion: Waist circumference (p<0.001), body mass index (p<0.001), systolic (p=0.014) and diastolic blood pressure (p<0.001), insulin (p<0.001) and triglyceride (TG) levels (p<0.001) were higher in the group with acrochordons. The presence of MetS was found as 71.6% in patients with acrochordon and 40.8% in controls (p<0.001). Conclusions: Patients with acrochordons should be evaluated in terms of the presence of MetS and its components. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.35-41